Effect of Sg. Lembing morphology due to sedimentation and extreme flood event - Nadiatul Adilah, Ahmad Abdul Ghani; Nor Farahin, Muhammad Azman Shah (Bahagian Hal Ehwal Akademik, Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
A study on river morphology was conducted at Sg. Lembing, Kuantan, Pahang. The major contribution to the depositional process in the river is the sediment which is composed by granular materials that have variety size and type. Excess sediment could cause the river level increase that can cause changes of the river morphology. This study focused on changes of river morphology by determines the point of the river that has major changes. Three sampling Stations have been chosen based on the river changes between in year 2010 to 2015 which had been analyzing using Google Earth software. The locations of study area are in upstream (Station 1), mid-stream (Station 2) and downstream (Station 3). Sampling data are collected in two day which is on 16 March 2016 and 23 March 2016. Sediment particles in every station were classified based from United State Army Corps Engineer [1] table. The data from Department of Irrigation and Drainage and Malaysian Meteorological Department are used for analysed rainfall pattern. As the conclusion, sediment sizes at Sg. Lembing are between 2.360mm to 0.425mm. The minimum and maximum total yearly rainfall data is 1443mm and 3775.5mm at 2008 and 2011 respectively.